Strategic Planning and Performance of Nigerian SMEs: The Moderating Role of Entrepreneurial Characteristics - G., Makinde Olubisi; U., Asikhia Olalekan (Journal of Economics and Behavioral Studies, 2018)
Studies that considered the moderating effect of entrepreneurial characteristics on the relationship between strategic planning and performance of SMEs are few. This research is aimed at investigating the relationship between strategic planning and SME performance while also considering the moderating effect of entrepreneurial characteristics on the relationship between these two variables. The study employed the use of survey research design using the owners/managers of 4,535 SMEs registered with SMEDAN as the target population. Correlation analysis was used to establish the extent of the relationship between strategic planning and performance of SMEs while hierarchical regression analysis was used to establish the moderating effect of entrepreneur characteristics on the relationship. Findings showed that there exist a statistically significant positive relationship between strategic planning and performance of SMEs in Lagos State, the study also indicated that entrepreneurial characteristics significantly moderates the relationship between strategic planning and performance of SMEs. The study concluded that entrepreneurial characteristics being exhibited influenced the performance of the business. Policy implications and recommendations were made.